Personal data as a market commodity: legal irritants from China’experience. - Giulio Santoni (European Journal of Privacy Law & Technologies, 2023)
This paper examines the legal challenges surrounding the treatment of personal data as a market commodity, with a specific focus on China's experience. The study begins with a comprehensive literature review and outlines the methodology employed. The paper then delves into the gradual construction of personal data protection in China, highlighting the evolution of laws and regulations in response to the growing importance of personal data protection in the digital age. It explores the development of legal frameworks and the establishment of regulatory bodies to safeguard individuals' personal information. This paper provides a comprehensive analysis of the theoretical framework surrounding the treatment of personal data as a market commodity in China. It highlights the gradual construction of personal data protection, explores the use of private law tools, and examines the economic circulation of personal data. Additionally, it discusses the role of public governance tools and offers insights into the challenges and potential solutions in this evolving landscape. Il presente lavoro esamina le questioni legate all’ inquadramento dei dati personali come bene, con un'attenzione specifica all'esperienza cinese. Lo studio inizia con un'ampia rassegna della letteratura e delinea la metodologia impiegata. Si addentra poi nella graduale costruzione della protezione dei dati personali in Cina, evidenziando l'evoluzione di leggi e regolamenti in risposta alla crescente importanza della protezione dei dati personali nell'era digitale. L’articolo fornisce infine un'analisi completa del quadro teorico che circonda il trattamento dei dati personali come merce di mercato in Cina. Mette in evidenza la graduale costruzione della protezione dei dati personali, esplora l'uso di strumenti di diritto privato ed esamina la circolazione economica dei dati personali. Inoltre, discute il ruolo degli strumenti di governance pubblica e offre approfondimenti sulle sfide e sulle potenziali soluzioni in questo panorama in evoluzione.